The quality of in-company training - perspectives and effects - Krötz, Maximilian [Verfasser] (My University, 2023)
"Vocational education and training plays a key role in providing a skilled workforce and in fighting youth unemployment. However, vocational training systems throughout the world experience problems with ensuring high quality training and limiting drop-out. Additionally, gaps prevail in research on the impact in-company training quality exerts on the desired outputs, such as high competence levels and low drop-out rates. Resultingly, vocational training is sometimes referred to as a ‘black box’. Furthermore, studies suggest there are perceptual differences between different groups of actors, for example between trainees and training personnel. These different perspectives make interpreting the relevant research difficult since previous research has commonly concentrated on the trainee-related mono-perspective. Against this backdrop, further research aiming to overcome both shortcomings, (1) the mono-perspective approach that does not meet the challenges of an interactive training and (2) insufficient insights on the effects of incompany training quality on outputs (e.g., competence, drop-out), would be a good step toward making vocational training an attractive path for young adults and companies. To contribute to this objective, the four papers of this dissertation follow a two-step approach. Papers 1 and 2 investigate potential differences in the perception of in-company training quality between trainees and trainers. Papers 3 and 4 analyze the role of in-company training quality for specific outputs, namely drop-out intention and vocational competence." (Authors' abstract, BIBB-Doku)
Betriebliche Ausbildungsqualität - Perspektiven und Wirkungen
Keywords: S 1.3 Berufliche Erstausbildung; L 6 Qualität; P 2.3 Auszubildende; 370; Betriebliche Berufsausbildung; Ausbildungsqualität; Auszubildender; Ausbilder; Perspektive; Kompetenzentwicklung; Ausbildungsabbruch